1988
DOI: 10.1128/mcb.8.1.203
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of rat liver maturation in vitro by glucocorticoids.

Abstract: The biochemistry of liver maturation was studied by using the RLA209-15 fetal rat hepatocyte line that is temperature sensitive for maintenance of the differentiated fetal liver phenotype. At 33°C these cells were dedifferentiated; but at 40°C they were phenotypically differentiated and, like normal fetal hepatocytes, synthesized moderate levels of albumin and transferrin, high levels of authentic (69,000 and 73,000 molecular weight) rat fetal a-fetoprotein (AFP), and low levels of a 65,000-molecular-weight va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1988
1988
1998
1998

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…The increased concentration of circulating glucocorticoids in fetal serum just before birth may be a key regulatory signal for development of the liver. This view is supported by the recent demonstration that glucocorticoids can promote fetal liver maturation in vitro (8).…”
Section: Resultssupporting
confidence: 67%
“…The increased concentration of circulating glucocorticoids in fetal serum just before birth may be a key regulatory signal for development of the liver. This view is supported by the recent demonstration that glucocorticoids can promote fetal liver maturation in vitro (8).…”
Section: Resultssupporting
confidence: 67%
“…The effects of glucocorticoids on the differentiation of bone-derived cells in vitro are not limited to cells of the osteoblast lineage Chou et al, 1988;Grigoriadis et al, 1988;Grigoriadis et al, 1989;Ringold et al, 1986;Violette et al, 19901. It is our experience that the conditions which favour osteogenic differentiation in cultures of rat marrow stromal cells (continuous culture in the presence of dexamethasone) also permit the differentiation of adipocytes. This conclusion is based upon the appearance of cells in the cultures having the morphological characteristics of adipocytes and the detection of the adipocyte specific aP-2 mRNA [Bernlohr et al, 1984;Hresko et al, 1988;unpublished observations].…”
Section: Isolation Of Osteoblast-like Cell Populations From Glass Framentioning
confidence: 98%
“…On the other hand, the maturation of fetal hepatocytes can be monitored by the decreased expression of AFP and increased expression of albumin gene (Chou et al 1988). Both retinoic acid (RA) and glucocorticoids exert profound effects on liver specific gene expression and hepatocyte phenotype (Cook & Chiu 1986, Chou et al 1988, Wan et al 1994a). Previously, we have shown that all-írans-RA (i-RA), whose receptors belong to the steroid/thyroid hormone receptor family, enhanced the expression of AFP and albumin genes in McA-RH 8994 rat hepatoma cells.…”
Section: Introductionmentioning
confidence: 98%